A reappraisal of the works of Elisabeth Kubler-Ross - Afonso, Selene Beviláqua Chaves; Minayo, Maria Cecília de Souza (Ciência & saude coletiva, 2013)
This article presents a reappraisal of part of the works of Elizabeth Kubler-Ross, one of the most quoted authors addressing the end of life process, mourning and dying. Her work has contributed to a clearer understanding of these issues by health professionals, families, religious and lay people who handle and/or experience mourning. She has also been the subject of controversy related to ethical issues and the scientific rigor of her work. The books analyzed in this article are: On death and dying (1969); Questions and answers on death and dying (1971); Living with death and dying (1981); On children and death(1983); On life after death (1991) and Life lessons (2000).